Assessment of the groundwater suitability for irrigation near Al Kufa City and preparing the final water quality maps using spatial distribution tools - Al Maliki, Ali A.; Abbass, Zainab D.; Hussain, Hussain M.; Al-Ansari, Nadhir (Environmental earth sciences, 2020)
In many parts of the world, groundwater quality is decreasing due to urbanization industrialization and use of agricultures in rural areas. This subject has formed an urgent need to determine the suitability of groundwater for various purposes. The aim of this study is to determine a groundwater index for groundwater use for irrigation in agriculture. The study is carried out in an agricultural area; near Al Kufa city, North of Al Najaf province, Iraq. Many chemical variables are used in this model, including (total dissolved solids TDS, electrical conductivity EC, sodium Na, potassium K and iron Fe), in addition to some of the heavy metals (cadmium Cd, lead Pb, chromium Cr, and nickel Ni), that also added to the index. The weight’s parameters are determined using analytical hierarchy process (AHP) and classified into five groups based on the human health significance of these parameters and negative effect on agriculture. The result of this study indicates that the water quality index (WQI) records values between (0 and 4.33), and in which the value of (2.16) represents the limit between unpolluted and polluted groundwater. This study confirms that all groundwater samples over the study area are suitable for agriculture. The final WQI values are exported to ArcMap environment to prepare the final WQI maps of study area.